Use of Vagus Nerve Stimulation and Vagal Maneuvers as Adjuvant Therapy for COVID-19 Patients - Susana Mabel Sendin; Juan Sebastian Yakisich (Ital Publication, 2021)
At present there is no effective specific antiviral drug to treat the ongoing COVID-19 pandemic that has already infected millions of individual and caused hundreds of thousand deaths worldwide. There is strong indication that a cytokine storm is responsible for the severity of COVID-19 patients. Pilot studies using IL-6 receptor inhibitors such as Tolicizumab have shown promising results. However, since the cytokine storm is a complex systemic inflammatory response involving multiple cytokines it can be hypothesized that a "paninhibition" of cytokines and/or cytokine receptors will be more effective. However, at the same time this strategy may cause more adverse effects. In this article, we propose the application of Vagus Nerve Stimulation (NVS) and/or some forms of vagal maneuvers as adjuvant therapies to prevent and/or mitigate the cytokine response in COVID-19 patients. This proposal is based on the ability of NVS and to decrease the production of IL-6 and other cytokines. The potential application of the diving response (one form of vagal maneuver), that has been shown to confer intrinsic resistance to inflammation in the blood of diving mammals, is also discussed as adjuvant therapy for COVID-19 patients.   Doi: 10.28991/SciMedJ-2021-03-SI-2 Full Text: PDF